2011
DOI: 10.1071/wf08183
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of vegetation, soil moisture and bulk density on depth of burning of thick organic soils

Abstract: The boreal biome is characterised by extensive wildfires that frequently burn into the thick organic soils found in many forests and wetlands. Previous studies investigating surface fuel consumption generally have not accounted for variation in the properties of organic soils or how this affects the severity of fuel consumption. We experimentally altered soil moisture profiles of peat monoliths collected from several vegetation types common in boreal bogs and used laboratory burn tests to examine the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
183
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 45 publications
11
183
0
Order By: Relevance
“…Yet, only a few studies have quantified combustion losses in pristine northern peatlands [30][31][32] . Previous studies have shown that depth of burn is primarily controlled by fire weather, soil moisture and seasonal ice conditions, as well as fuel bulk density 30,31,33 . In general, the combustion values measured in our pristine plots (2.0 ± 0.5 kg C m − 2 ) were consistent with these previous studies, in which combustion rates averaged 2.4 kg C m − 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, only a few studies have quantified combustion losses in pristine northern peatlands [30][31][32] . Previous studies have shown that depth of burn is primarily controlled by fire weather, soil moisture and seasonal ice conditions, as well as fuel bulk density 30,31,33 . In general, the combustion values measured in our pristine plots (2.0 ± 0.5 kg C m − 2 ) were consistent with these previous studies, in which combustion rates averaged 2.4 kg C m − 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For wildfires, similar critical values have been found associated to fuel moisture (Frandsen, 1997;Rein et al, 2008;Benscoter et al, 2011;Watson and Lovelock, 2013;Watts, 2013). Atmospheric oxygen and fuel moisture are two of the most crucial factors governing the ignition and spread of wildfires throughout Earth's history, more important than other properties like mineral content, chemical composition, and bulk density.…”
Section: Introductionmentioning
confidence: 60%
“…Atmospheric oxygen and fuel moisture are two of the most crucial factors governing the ignition and spread of wildfires throughout Earth's history, more important than other properties like mineral content, chemical composition, and bulk density. Organic soils like peat are porous and are able to hold a wider range of moisture contents 1 (MC), ranging from about 10% under drought conditions to well in excess of 300% under flooded conditions (Benscoter et al, 2011;. Similar to flaming fires, the fuel moisture represents a significant energy sink to prevent smouldering fires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…resulted in lower depth of burn, and, consequently, in lower forest floor fuel consumption (FFFC) in comparison with other boreal forest types [36]. In the CanFIRE model, FFFC is a function of duff load and climate conditions [37], and does not consider the lower depth of burn for calculations. Therefore, FFFC equations had to be modified to reflect specific carbon emission in BS forests dominated by Sphagnum spp.…”
Section: Simulation Of Carbon Emissions By Firementioning
confidence: 99%